Chemiluminescence-based characterization of heat release rate dynamic in a micro gas turbine combustion chamber. (June 2022) - Shen, Wenkai; Xing, Chang; Liu, Li; Hu, Qiming; Wu, Guohua; Yang, Yujia; Wu, Shaohua; Qiu, Penghua; Wu, Jiangquan
Abstract: Chemiluminescence is a major spontaneous emission inflame and can be used in combustion diagnostics to evaluate various flame characteristics. OH∗ chemiluminescence is a good indicator for heat release rate analysis in alkane flames. In this paper, a high-resolution ultra-violet imaging system was used to capture the OH∗ chemiluminescence images. The experiments were conducted in a pilot-scale system with a 300 kW combustion chamber. The variety of temperature distribution is evaluated using the outlet temperature distribution factor. The heat release rate dynamic characteristics were discussed by criteria of distribution uniformity on the spatial and temporal dimensions and the characteristic frequency results obtained by three different methods. The result shows that operating conditions with a uniform outlet temperature distribution always have more uniform spatial distribution and smaller temporal fluctuation amplitude of heat release rate. Frequency results obtained by different methods match very well when the heat load ratio is over 70%. The flame frequency characteristics correlate well with the turbulence property compared with the unmixedness of fuel and air. But the oscillation amplitude of heat release is mainly affected by the unmixedness. Highlights: MGT part-load performance is limited by flame dynamic characteristics. Discussion of HRR dynamic characteristics based on chemiluminescence. Consideration of HRR spatio-temporal distribution property and dynamic characteristic. Spatio-temporal distribution of temperature can be improved by changing unmixedness. Flame dynamic characteristics correlate well with turbulence characteristics.